Political Review by Parliament to Government Regulations in Lieu of Laws that have Been Tested by the Constitutional Court - M. Husnu Abadi (Rechtsnormen: Journal of Law, 2024)
Background. The principle of the rule of law is embraced by Indonesia, which declares itself as a state of law, the 1945 Constitution of the Republic of Indonesia authorizes the Constitutional Court to test laws against the basic law. Method. This study is a normative study, with the approach of legislation and several cases. The type of data used is secondary data, with descriptive qualitative analysis. Results. The results of the study state that the use of the authority to review Perpu by the Constitutional Court is a material change in the constitution, which can reduce or deprive the constitutional rights of the DPR in using political review, or can cause the Perpu to be determined by the DPR is not in accordance with the original, because it has been tested first by the Constitutional Court. Conclusion. However, when the Constitutional Court, as the interpreter of the Constitution, declared its authority to test the constitutionality of Perpu, controversy arose: The Constitutional Court has deviated from the Constitution, and on the contrary, the Constitutional Court has been correct in interpreting the Constitution even though it has increased its authority.